Melawan Korupsi dengan Prinsip Islamic Governance - Baya Risqiya (Getpress Management Journals, 2025)
Corruption is a social disease that undermines the fabric of the state and weakens public trust in government institutions. In Muslim-majority countries, corruption is often a major challenge even though Islamic teachings strictly prohibit all forms of fraud, abuse of power and embezzlement of public assets. This article aims to examine how Islamic principles, particularly in the context of Islamic governance, can serve as a normative and practical paradigm in the fight against corruption. Using a qualitative-comparative study approach, this article synthesizes classical and contemporary literature on Islamic Governance and analyzes its application in several Muslim countries such as Saudi Arabia, Malaysia, Indonesia, Turkey, and Nigeria. It is found that Islamic Governance rooted in the principles of amanah, hisbah, justice, shura, and maslahah can be an alternative model for building a clean, fair, and integrity government.